Evaluation of Complexity of ECG Parameters Using Sample Entropy and Hankel Matrix - Šliupaitė, A.; Navickas, Z.; Vainoras, A. (Elektronika ir Elektrotechnika, 2009)
A lot of diagnostics criteria are collected by registration and analysis of electrocardiogram (ECG)parameters. Evaluating the complexity of the signal is an important method in cardiology. In order to get more accurate evaluations of complexity it is purposive to use qualitatively different methods of cardio-signal analysis. In this paper, complexity is presented as a statistic estimate and expressed as ag special alebraic function. Both methods gave similar results. Important tendencies of complexity change were observed, specified by age and workload influence on heart work. More detailed analysis of complexity change will be performed in further research. Ill. 8, bibl. 8 (in English; summaries in English, Russian and Lithuanian).